EDUKASI POLA MAKAN PADA IBU BALITA UNTUK PENINGKATAN STATUS GIZI BALITA DI WILAYAH PUSKESMAS DADOK TUNGGUL HITAM KOTA PADANG - Azrimaidaliza Azrimaidaliza; Welly Femelia; Annisa Dwi Apriliani; Zikrabi Hidayat (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
The problem of nutritional status in toddlers is a major concern worldwide, especially in developing countries such as Indonesia. Feeding difficulties in toddlers can cause nutritional status problems. Parents, especially mothers, play an important role in meeting their children's nutritional needs. Nutritional education activities aim to increase the knowledge of mothers of toddlers regarding good eating habits for improving the nutritional status of their children. The method used was direct counseling using leaflets as a medium, targeting mothers of toddlers who attend the Posyandu XIV Megamerian working in Puskesmas Dadok Tunggul Hitam, Padang City. 15 mothers of toddlers attended the activity, one health worker from Puskesmas Dadok Tunggul Hitam, two cadres, and four volunteers. Monitoring and evaluation were conducted by comparing the pre-test and post-test scores of the mothers of toddlers. Based on the results obtained, there was an increase in the average pre-test and post-test scores, from 45.56 to 61.11, with a statistical test result of p = 0.043. From these results, it can be concluded that providing nutritional education regarding good eating habits through leaflets can improve the knowledge and understanding of mothers of toddlers. Furthermore, this activity is expected to improve feeding and childcare behavior in toddlers. As a follow-up, nutritional education activities can be held regularly through Posyandu activities to overcome nutritional problems in Indonesian toddlers. In addition, the role of the community and support from relevant parties are also needed to improve the nutritional status of toddlers in this country.